Elijah's Cave on Mount Carmel and its inscriptions - Ovadiah, Asher, (Archaeopress Publishing Ltd, 2015)
Literary sources suggest that Mount Carmel was a sacred site for the pagans, for the veneration and worship of Ba'al, as practiced there since the 9th century BCE through the erection of altars and temples/shrines in his honour. This work examines this topic.